A communicative property with its industrial applications. (9th March 2017) - Riaz, Muhammad; Abbas, Nasir; Mahmood, Tahir
Abstract : This study presents a relationship between two well‐known distributions, namely, geometric and binomial distributions. We will provide the statement of our result supported by its precise proof. In addition, we will give an illustrative example to explain the suggested relationship. We will indicate some industrial applications where the derived communicative property may be used. Moreover, the use of this linkage property will be shown in control charting setup.